Psychological treatment of problematic sexual interests: cross-country comparison - Klapilová, Kateřina; Demidova, Liubov Y; Elliott, Helen; Flinton, Charles A; Weiss, Petr; Fedoroff, J Paul (International review of psychiatry, 2019)
This paper reviews the use of psychotherapeutic approaches to treat individuals who have committed sex crimes and/or have problematic sexual interests (PSI); including types of psychotherapy used, descriptions of preventive and reintegration programmes, and highlighting specific theoretical controversies. In the second part, experts from Canada, the Czech Republic, Russia, the United Kingdom, and the United States, who participated in an International Consensus Meeting held in Prague (2017), summarize treatment programmes in their countries. The comparison revealed some general findings: each country has variability between its own programmes; most countries have different programmes for people who are in custody and who are in the community; the state-directed treatment programmes are primarily focused on criminal individuals, while non-criminal individuals are treated in preventive programmes and/or in special clinics or are untreated; the presence of PSI in patients is acknowledged in most programmes, although specific programmes exclusively for individuals with PSI rarely exist. Studies on effectiveness are difficult to compare due to methodologic, political, and cultural differences. Further communication between more countries to share knowledge about successful treatments and preventive approaches is needed, especially enhanced international collaboration between researchers and clinicians to verify the effectiveness of current clinical and experimental program, rs.
Keywords: Psychotherapy; Česká republika; Paraphilic Disorders; zločinci; United Kingdom; lidé; North America; psychoterapie; parafilie; Severní Amerika; srovnání kultur; Spojené království; Criminals; Czech Republic; Cross-Cultural Comparison; Humans